Motivation and behaviour change in Parkrun participants in Western Cape, South Africa - Chivunze, Edgar (University of Cape Town, 2021)
Background: Participation in physical activity is a cost effective way to reduce the risks of over 25 chronic diseases. Despite the many dangers of physical inactivity, more than a quarter of the South African population remains inactive. One initiative aimed at increasing engagement in physical activity is parkrun, a free weekly 5 km running/walking based activity. There has been an increase in the number of parkrun participants in South Africa since its inception. An understanding of the motivation for participation and health related behaviour change is important for organisers and public health professionals to increase participation in this weekly mass participation event. Aim: The aim of this study was to describe the motivations for participation in parkrun and physical activity related behaviour changes among parkrun participants registered in the Western Cape Province of South Africa. Specific objectives The specific objectives of this study were: to identify demographic characteristics of parkrun participants in the Western Cape Province of South Africa; to describe the motivations for participating in parkrun runs in the Western Cape Province of South Africa; and to investigate physical activity related behaviour changes as a result of participating in parkruns in South Africa's Western Cape Province based on pre and post participation physical activity levels Methods: A cross sectional study was performed on 1787 parkrun participants registered at 40 parkrun sites in the Western Cape Province of South Africa. Participants from 37 of these sites were invited to participate via the parkrun South Africa mailing list in an online survey. Participants from the remaining three parkrun sites responded on paper-based questionnaires at the parkrun sites. The questionnaire included sections on demographic characteristics including employment status, gym membership and educational level; physical activity programmes before joining parkrun and changes in physical activity after joining parkrun. Results: The median age of participants was 50 (IQR:38-59). Female participants formed 53.3% of the sample. Approximately 80% of participants were educated to diploma or degree level (Technikons/College/University); and participants reported high employment rates (71%). Fifty-one percent of the sample were gym members. A total of 64.8% reported having very good to excellent health. A total of 86.1% reported health/fitness as the biggest motivation for participation in parkrun. Another 71.8% of the sample were motivated by enjoyment. Safe environment (58.7%), earning Discovery Health Vitality Points (46.4%), stress relief (40.8%), cost (40.4%) and socialisation (39.4%) were other common motivations among the sample. After joining parkrun, 24% of participants took up new physical activity programmes, with a further 24% of participant increasing their weekly volume of physical activity. More female participants (50.9%) than male participants (44.7%) increased their physical activity levels or took up new physical activity programmes (χ² =7.331, p=0.007). Running was the widely adopted physical activity attracting 18.2% of the sample as new runners. Conclusion: In conclusion, we found that parkrun in the Western Cape is mostly taken up by participants in their sixth decade of life with half of them being overweight. Most participants are physically active before joining parkrun with more than half exceeding recommended global physical activity levels. These results were described in previous studies in Australia and the UK. We also found health/fitness to be the biggest motivation for parkrun participation followed by enjoyment and the safe environment provided at parkrun sites. Running and walking are the common activities that are taken up by participants after joining parkrun. Further prospective studies are recommended to determine cause and effect models and describe health related physical activity behaviour changes in detail.